The development of CD8 T-cell exhaustion heterogeneity and the therapeutic potentials in cancer - Zhang, Junfeng; Lei, Feifei; Tan, Huabing (Frontiers in Immunology, 2023)
CD8+ T cells are essential lymphocytes with cytotoxic properties for anti-tumor immunotherapy. However, during chronic infection or tumorigenesis, these cells often become dysfunctional, gradually losing their ability to release cytokines and exhibiting reduced cytotoxicity, a state referred to as “T cell exhaustion." This unique state was characterized by the increasing expression of inhibitory checkpoint receptors, and interventions targeting immune checkpoint blockades have been considered a promising strategy to stimulate T cell killing. Recent investigations have demonstrated that exhausted T cells not only display functional, metabolic, transcriptional, and epigenetic differences but also comprise a heterogeneous group of cells. Here, we review the characteristics of the exhausted CD8+ T cell heterogeneity during chronic infection and tumorigenesis and present recent findings on the developmental trajectory of T cell exhaustion. Additionally, we explore how these unique subsets dictate responses to immunotherapy and discuss potential strategies for enhancing the efficacy of immune checkpoint blockades in cancer by leveraging exhausted T cell heterogeneity.